2014
DOI: 10.1055/s-0034-1367020
|View full text |Cite
|
Sign up to set email alerts
|

Ärztlicher Bereitschaftsdienst in Deutschland: Befragung von Bereitschaftsdienstärzten zur gegenwärtigen Situation (Kritische Aussagen)

Abstract: Based on reported views from survey respondents, urban and rural primary care service needs vary significantly and, therefore, different solutions are needed to improve out-of-hours primary care and optimise service quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This is in line with findings reported by Briggs et al [ 34 ]. In this context, low contacts to specialists and the OOHC seem to be not surprising due to the fact that NH visits by specialists are—depending on their specialization—insufficient in Germany [ 35 , 36 ] and the financial compensation for participating in the OOHC is criticized as too low by physicians [ 13 ]. Both facts may contribute to the low presence/relevance of these physicians in the management of NHRs’ health changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with findings reported by Briggs et al [ 34 ]. In this context, low contacts to specialists and the OOHC seem to be not surprising due to the fact that NH visits by specialists are—depending on their specialization—insufficient in Germany [ 35 , 36 ] and the financial compensation for participating in the OOHC is criticized as too low by physicians [ 13 ]. Both facts may contribute to the low presence/relevance of these physicians in the management of NHRs’ health changes.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly care physicians as in the Netherlands, for example [ 12 ] are an exception. In the case of health deteriorations outside of GPs’ working hours, nursing staff can contact out-of-hour health care services (OOHC) in which every practicing physician is legally obliged to participate [ 13 ]. In Germany, the OOHC can be called by the nationwide phone number “116 117”.In life-threatening cases, the Emergency Medical Service (EMS) is responsible and can be contacted to send out an ambulance (“112”).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, approximately 110,000 of these physicians who worked in regular care -thereof 35,100 GPs and 11,500 internists worked additional in OOHC, except for doctors’ with chronic diseases and in-patient physicians [ 6 ]. A recent study with German GPs views on the situation in OOHC reported on critical issues, in particular highlighting that OOHC is one primary factor making the role as a GP in Germany unattractive [ 7 ]. Unfortunately, there are no data available which show the workload of physicians who worked in OOHC and regular care.…”
Section: Introductionmentioning
confidence: 99%
“…A total number of about 210 GPs to be invited to participate in the process evaluation will be expected [ 8 ]. Based on previous data, a response rate of 45% is assumed, reducing the sample size to about 95 GPs [ 20 22 ]. Qualitative x (I, O) x (O) x (I, O) x (I, O) GPs who participate in the main trial and agree to participate in the process evaluation.…”
Section: Methodsmentioning
confidence: 99%